2015
DOI: 10.1016/j.buildenv.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal performance of wood-hemp insulation in timber frame wall panels with and without a vapour barrier

Abstract: An in situ experiment on a full-scale timber frame test building was carried out to study the hygrothermal performance of wood-hemp composite insulation in timber frame wall panels with and without a vapour barrier. The heat transfer properties and the likelihood of mould growth and condensation in the panels were compared. Step changes in the internal relative humidity were performed to explore the effects of high, normal and low internal moisture loads on the wall panels. No significant difference in the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…These components can be separated either by retting including chemical and microbial actions or mechanically, dividing the stem into bark fibres and woody stem (shiv) fractions. These materials have the potential to act as a building material to moderate humidity levels in an indoor environment due to their inherent hygroscopic properties (Latif et al 2015;Laborel-Préneron et al 2016;Hurtado et al 2016;Bourdot et al 2017). The components of fibres and shiv of flax and hemp include cellulose, hemicellulose, lignin, pectin, waxes and water soluble substances.…”
Section: Introductionmentioning
confidence: 99%
“…These components can be separated either by retting including chemical and microbial actions or mechanically, dividing the stem into bark fibres and woody stem (shiv) fractions. These materials have the potential to act as a building material to moderate humidity levels in an indoor environment due to their inherent hygroscopic properties (Latif et al 2015;Laborel-Préneron et al 2016;Hurtado et al 2016;Bourdot et al 2017). The components of fibres and shiv of flax and hemp include cellulose, hemicellulose, lignin, pectin, waxes and water soluble substances.…”
Section: Introductionmentioning
confidence: 99%
“…firstly, they are included in relative humidity variation protocols for standard adsorptiondesorption tests such as Nordtest [27] and ISO 24353 [28], secondly, the results can be compared with some of the in situ tests carried out using the same relative humidity variation protocol [11,29]. The time for each step of relative humidity condition was sufficient for the insulation materials to reach equilibrium moisture content.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…When the insulation materials were removed from the framework, water deposits on the lower surface of the framework of the Stone Wool insulation were also noticed, implying that further condensation had occurred in the Stone Wool insulation setup during the experiment. It was not possible to measure the amount of condensate resulting from the experiments but another study by the authors [29] did examine this aspect. Condensation seemed to occur in the acrylic surface of the Hemp-acrylic interface 36 (±1) hours later than it occurred in the Stone Wool-acrylic interface (Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…They showed that moisture accumulation was observed in the layer close to the plaster for the wall without Oriented Strand Board (OSB). Latif et al [16] carried out an in situ experiment on a full-scale timber frame test building to study the hygrothermal performance of wood-hemp composite insulation in timber frame wall panels with and without a vapor barrier. They observed a very low impact on the U-value for the stresses studied.…”
Section: Introductionmentioning
confidence: 99%